Is V–Y plasty necessary for penile lengthening? Girth enhancement and increased length solely through circumcision: description of a novel technique - Mertziotis, Nikos (Nature Publishing Group, 2013)
Our objective is to describe a novel ligamentolysis approach using a subcoronal incision technique and to determine its safety and efficacy. During the last 7 years, 82 consecutive patients had penile augmentation surgery. Ligamentolysis, through a lower abdominal incision (V–Y plasty) in the first 35 males, was performed (Group A), followed by circumcision ligamentolysis in the next 47 males (Group B). The operation time, complications, and the preoperative and postoperative values of penile length and girth along with the self-esteem and relations questionnaire score as well as satisfaction score was calculated before and after the surgery, and a comparison was conducted between the groups. The mean age at presentation was 32 years (range: 18–56 years). Seventy-nine patients suffered from penile dysmorphophobia, and three patients had micropenises (length <7.5 cm). The mean surgical times were 150.7 and 125.2 min for Groups A and B, respectively (P=0.005). Postoperatively, four Group A patients and three Group B patients (11% versus 6%, respectively) experienced penile retraction (P=0.453). Hypertrophic scars were observed in 18 men (51%) in the latter group. In the circumcision group, no major wound complications were recorded. The length and girth improvements between the groups were similar. In terms of satisfaction and SEAR improvement, the resulting difference for both variables favored the circumcision group (P=0.007 and <0.001, respectively). With strict selection criteria, the circumcision ligamentolysis procedure compared to the V–Y plasty demonstrated improved results in terms of safety, operation time, retraction rate and cosmetic appearance without any compromise in the gained penile size.